The Effect of Unemployment on Self-Reported Health and Mental Health in Greece from 2008 to 2013: A Longitudinal Study Before and During the Financial Crisis - Nick Drydakis (Institute for the Study of Labor (IZA), 2014)
The current study uses six annual waves of the Longitudinal Labor Market Study (LLMS) covering the 2008-2013 period to obtain longitudinal estimations suggesting statistically significant negative effects from unemployment on self-reported health and mental health in Greece. The specifications suggest that unemployment results in lower health and the deterioration of mental health during the 2008-2009 period compared with the 2010-2013 period, i.e., a period in which the country's unemployment doubled as a consequence of the financial crisis. Unemployment seems to be more detrimental to health/mental health in periods of high unemployment, suggesting that the unemployment crisis in Greece is more devastating as it concerns more people. Importantly, in all specifications, comparable qualitative patterns are found by controlling for unemployment due to firm closure, which allows us to minimize potential bias due to unemployment-health related reverse causality. Moreover, in all cases, women are more negatively affected by unemployment in relation to their health and mental health statuses than are men. Greece has been more deeply affected by the financial crisis than any other EU country, and this study contributes by offering estimates for before and during the financial crisis and considering causality issues. Because health and mental health indicators increase more rapidly in a context of higher surrounding unemployment, policy action must place greater emphasis on unemployment reduction and supporting women's employment.
Keywords: C23; C33; E24; I12; 330; self-reported health; self-reported mental health; unemployment; financial crisis